Effects of clinical medications on male fertility and prospects for stem cell therapy - Mo, Peiting; Zhao, Ziran; Ke, Xinpeng; Fan, Yong; Li, Chaohui (Frontiers in Cell and Developmental Biology, 2023)
An increasing number of men require long-term drug therapy for various diseases. However, the effects of long-term drug therapy on male fertility are often not well evaluated in clinical practice. Meanwhile, the development of stem cell therapy and exosomes treatment methods may provide a new sight on treating male infertility. This article reviews the influence and mechanism of small molecule medications on male fertility, as well as progress of stem cell and exosomes therapy for male infertility with the purpose on providing suggestions(recommendations) for evaluating the effect of drugs on male fertility (both positive and negative effect on male fertility) in clinical application and providing strategies for diagnosis and treatment of male infertility.